Wacana Pluralisme Dalam Berita Perang Air (cian cui) di antarariau.com - Firmanto, Firmanto; Yesicha, Chelsy (Komunika : Jurnal Ilmiah Komunikasi, 2024)
In Riau there are several cultures, traditions, and festivals that are used as icons of Riau's distinctive tourism and have captivated foreign eyes, one of which is the Water War Festival (cian cui) which was created by local residents about 10 years ago (antarariau.com). This Water War Festival begins with the Chinese community game when the Chinese New Year. Then Antarariau.com made a discourse on pluralism based on the water war festival. Then the aim of the researcher in this study was to find out the structure of the text on the news of Air war (Cian cui) in the news portal antarariau.com. which contains elements of pluralism, to find out the practice of discourse in the news of the water war on the news portal antarariau.com. which contains elements of pluralism, to find out social practices in the news of water war on the interariau.com news portal. which contains elements of pluralism. In this study using qualitative methods. using Norman Fairclough's Theory. This theory sees the formation of a discourse / discourse in various dimensions that are inseparable from one another. Research locations in Antarariau.com are from 2017 to 2018. Air war news in Antarariau.com is dissected using Norman Fairclough's Theory and is described based on the concept of pluralism. The object in this study is the news portal www.antarariau.com and the subject of this research is the news of the water war (cian cui) in Selatpanjang. Data collection techniques used are documentation and interviews. Data validity checking techniques use triangulation and extension of participation. The results of this study indicate that in the reporting of the war on water (cian cui) in the Kota Selatpanjang , the length of the Kepualauan Meranti, antarariau.com displays more activities or activities that contain elements of pluralism. The structure of the text in the seven analyzed news contains elements of tolerance, openness, equality, and wisdom. Then Antarariau.com managed to summarize the discourse of pluralism in the news of the water wars in the Meranti Islands. Finally, there is an element of pluralism in the practice of discourse or social practices established by Antarariau.com when establishing a discourse on pluralism in the news of the Water Warfare Festival.